Analisis Daya Dukung Tanah Terhadap Kerusakan Jalan di Desa Bulutigo Kecamatan Laren Kabupaten Lamongan - Miftahul Harits Abdullah; Rio Rahma Dhana (Jurnal Teknika, 2021)
Road damage in Bulutigo Village, Laren District, Lamongan Regency affects access to agricultural mobilization in Lamongan Regency. So the researchers studied the value of the carrying capacity of the soil that caused road damage on the Bulutigo Village road, Laren District, Lamongan Regency. This study also examines the factors that affect the decline in the value of the bearing capacity of the soil. Data processing shows that the road subgrade soil in Bulutigo Village, Laren District, Lamongan Regency has a low carrying capacity value in terms of water content testing with an average value of 16.66% which includes high water content, from the Atterberg limit, it is included in the class of clay soil type. has a high plastic value with a PI value of 34.61%. Meanwhile, in the CBR test, the CBR value was 6.80% which was included in the "enough" category. And in the direct shear strength test, the value of the internal shear angle () is 15.03o.